PENGARUH MOTIVASI BELAJAR DAN GAYA BELAJAR TERHADAP PRESTASI BELAJAR SISWA SMP SWASTA SE-KOTA TANGERANG PADA PELAJARAN BAHASA INGGRIS - Elawati Elawati; Muljadi; Sutrisno (Dhammavicaya : Jurnal Pengkajian Dhamma, 2023)
This study aims to examine 1) Is there an effect of learning motivation on learning achievement, 2) is there an effect of learning style on learning achievement, and 3) is there an effect of learning motivation and learning style on learning achievement together. This type of research includes quantitative research with conclusions drawn through statistical analysis. The research location is in private junior high schools throughout the city of Tangerang, the population is 263 students, and the research sample is 159 students. Based on the results of the study: (1) There is a positive and very significant effect between Learning Motivation (X1) on Learning Achievement (Y) with a correlation coefficient score of ry1 = 0.773a, the influence of High Motivation (X1) will have a strong influence on Learning Achievement (Y) private junior high school students in the city of Tangerang with a determination coefficient score of r2y1 = 0.595. 2) There is a positive and very significant relationship between Learning Style (X2) on Learning Achievement (Y) of private junior high school students in the city of Tangerang, with a correlation coefficient score of ry2 = 0.761a, on Learning Style (X2) High will provide a strong relationship on the increase in Learning Achievement (Y), with a coefficient of determination score produced by r2y2 = 0.579. 3) and there is a positive and very significant effect between motivation (X1) and learning style (X2) together on learning achievement (Y) with a correlation coefficient score of ry1.2 = 0.799a, the effect of learning motivation (X1) and Learning style (X2) together with strong learning achievement (Y) will have a large relationship with learning achievement (Y), with a determination coefficient score of r2y3 = 0.639. Contribution or influence of 6.39%, the remaining 36.1% was contributed by other variables that have a relationship with increasing learning achievement (Y).